A STUDY ON STUDENTS’ ABILITY IN UNDERSTANDING CONDITIONAL SENTENCES AT SECOND GRADE OF SMK N 1 TEMBILAHAN ACCOUNTING 3 MAJORING - Siti Barliana; Edi Ardian; Syafrizal (J-Shelves of Indragiri (JSI), 2021)
This study is concerned with the students’ ability in understanding Conditional Sentences. It was done for the second-grade students of SMK N 1 Tembilahan. Then this research used a descriptive research that supported by quantitative approach. The research populations were taken from all the students of the second-grade of SMK N 1 Tembilahan in academic year 2020/2021. The total of populations were 108 students, which consist of three classes. The researchers selected a class as the sample is XI Accounting 3 (36 students). The instrument used to collect the data is test. It consisted of fifty multiple choices questions. Based on the analysis, the students’ ability scores in understanding conditional sentences is 84.38 in the type 1, 96.92 in the type 2, and 97.35 in the type 3. Their mean scores in understanding conditional sentences is 98.12. The research result is the students’ ability in understanding conditional sentences is in ranging very good level. It means that they have understood conditional sentences.